Lys-des[Arg 9 ]–Bradykinin Alters Migration and Production of Interleukin-12 in Monocyte-Derived Dendritic Cells - Gulliver, Rosalind; Baltic, Svetlana; Misso, Neil L.; Bertram, Cornelia M.; Thompson, Philip J.; Fogel-Petrovic, Mirjana (American journal of respiratory cell and molecular biology, 2011)
This study tested the hypothesis that proinflammatory kinin peptides are involved in modulating human dendritic cell (DC) function. Inflammation is accompanied by an increased maturation of DCs and the generation of kinins, particularly Lys-des[Arg(9)]-bradykinin (Lda-BK). We assessed the role of Lda-BK in the activation and migration of human monocyte-derived DCs (hMo-DCs) matured through the use of LPS, TNF-α + IL-1β, or CD40 ligand. Kinin B(1) and B(2) receptor mRNA and protein expression were assessed by confocal microscopy, flow cytometry, and RT-PCR. The effects of Lda-BK on the migration of mature hMo-DCs were assessed in Transwell chambers, whereas the expression of costimulatory molecules and the secretion of IL-12 were assessed by flow cytometry and ELISA, respectively. The expression of the kinin B(1) receptor (B(1)R) was down-regulated during the maturation of hMo-DCs, whereas the expression of B(2)R was unchanged. The B(1)R agonist Lda-BK was not chemotactic for hMo-DCs matured using LPS, TNF-α + IL-1β, or CD40 ligand, but Lda-BK enhanced the secretion of IL-12p70 and inhibited the secretion of IL-12p40 by mature hMo-DCs. However, the exposure of hMo-DCs matured with TNF-α + IL-1β to Lda-BK for 6 hours decreased subsequent migration in response to Lda-BK, the chemokine CCL19, or Lda-BK combined with CCL19. The expression of B(1)R was increased in hMo-DCs from subjects with asthma compared with subjects without asthma, in keeping with a tendency toward increased in vitro migration of asthmatic hMo-DCs in response to Lda-BK. The increased formation of Lda-BK and the enhanced expression of B(1)R as a consequence of inflammation may alter the migration of mature, antigen-laden DCs to regional lymph nodes in response to CCL19, may modulate the secretion of cytokines by these DCs, and may contribute to the accumulation of mature DCs in the lungs of patients with asthma.